(untitled) (Annals of Medical Research, 2023)
Aim: Acute cholecystitis is the most common causes of acute abdomen in elderly population. This study aimed to present the early postoperative period (≤ 30 days) outcomes of elderly patients (≥ 65 years old) with acute cholecystitis who underwent early or delayed cholecystectomy. Materials and Methods: Between January 2016 and December 2020, 74 patients aged 65 and over underwent cholecystectomy for acute cholecystitis were included in the study. The patients were divided into two groups as early (time between diagnosis and cholecystectomy 7 days or less, n= 43, 58.1%) or delayed (time between diagnosis and cholecystectomy over 7 days, n= 31, 41.9%) cholecystectomy. Demographic characteristics, preoperative laboratory and radiological findings, and perioperative data of patients were evaluated, and the groups were compared. Results: The median age of patients was 73 (65-90) years, and 39 (52.7%) were male. Sixty-one (82.4%) patients underwent laparoscopic, 8 open (10.8%) and 5 (6.8%) conversion cholecystectomy. The rate of laparoscopic cholecystectomy was higher in the delayed group (n= 29, 93.5%) than in the early group (n= 32, 74.4%), but no statistically significant difference was detected (p=.06). The rate of open cholecystectomy was statistically significantly higher in the early group (n=8, 18.6%) than in the delayed group (n=0) (P=.017), the conversion rate was similar between the groups (p=1). There was no significant difference between the groups in terms of intraoperative complications (p=1). The length of hospital stay was statistically significantly longer in the early compared to the delayed group (5 (1-21) days and 2 (1-12) days, respectively, p< .001). Conclusion: There was no statistical difference regarding intraoperative complications in patients underwent early or delayed cholecystectomy. We believe that the patient’s clinical presentation and early or delayed cholecystectomy experience of the team are vital in determining the timing of cholecystectomy, as well as the severity of acute cholecystitis.